Systemic Thrombolysis for Treatment of Postpartum Saddle Embolism Complicated by Postpartum Hemorrhage: A Case Report and Brief Literature Review - Kathy Mostajeran; Hillary Boswell; Ziad Haidar (Case Reports in Obstetrics and Gynecology)
Venous thromboembolic events (VTE), specifically pulmonary embolisms, account for a significant portion of maternal morbidity and mortality. Due to the procoagulant physiological changes that occur, pregnancy and the postpartum period are known risk factors for thromboembolic events. The risk is greatest during the first-week postpartum and remains elevated for up to six weeks as compared to the general population. Treatment guidelines regarding the use of thrombolytics for massive pulmonary embolism occurring in pregnancy and the postpartum are not well established. In nonpregnant populations, thrombolytic agents are well known to decrease the mortality in the setting of a massive pulmonary embolism. However, in the absence of management guidelines, thrombolysis in pregnancy remains guided by case reports and case series. We present a case of a massive pulmonary embolism (PE) causing hemodynamic instability during the postpartum period treated with tissue plasminogen activator (tPA). The case was complicated by delayed postpartum hemorrhage successfully managed with the uterotonic methylergometrine. The patient was started on oral anticoagulation and continued for six months without recurrent VTE. Our case demonstrates a rare occurrence of a saddle embolism after a vaginal delivery within the first postpartum week which was successfully managed with the use of systemic thrombolysis and minimal intervention to manage the iatrogenic delayed postpartum hemorrhage. To the authors’ knowledge, no other similar case report exists. This case highlights the need to develop guidelines for the use of thrombolysis in mothers who present with massive pulmonary embolus and a noninvasive means to manage adverse bleeding events in the puerperium.